Safety in IBS contruction : A study on safety during precast concrete installation - Muhammad Qayyim Bin Suhaimi (School of Environmental Engineering, University Malaysia Perlis, 2014)
The safety aspect is very important in construction projects. Any construction projects such as the installation of precast concrete will accident if they are not concerned about safety aspect during the process of making the work as helmet, gloves and shoes.The goal of the project aims to find ways to avoid hazards and accidents to employees at the workplace, to identify the machines and equipment installed / used safely for workers and environmental conditions as well as provides recommendations for employees to follow instructions and installation of precast concrete in a way that correct.